PRECURSORY PHASES OF LARGE KAMCHATKAN EARTHQUAKES - Sobolev G.A. (My University, 2000)
Laboratory modeling showed that a macrofracture was preceded by typical acoustic emission phases. These are acoustic quiescence, gradual restriction of acoustic activity toward the future macrofracture location accompanied by clustering, and foreshock activation. These phases indicate the development of mechanical instability in the macrofracture volume. These ideas were tested by examining precursory seismicity before three M > 7 Kamchatkan earthquakes that had occurred during the last six years. The data base was a regional earthquake catalog with K ≥ 8.5 events completely reported for that time period. All earthquakes had been preceded by seismicity quiescences and foreshocks detected with the help of the predictive parameter RTL. The quiescent area had been observed 3.7 to 2.2 years before the earthquake and was about 200 km across. The epicenters were found to lie at the edge of the quiescent areas. The foreshock area had been observed 1.7 to 0.5 years before the main event and was about 50-100 km across. The epicenters were nearly at the centers of the respective foreshock areas. The earthquakes were preceded by clusters that consisted of two or more K ≥ 10 events occurring in the respective epicentral areas. These phenomena also occurred without being followed by large earthquakes. It is concluded that, although the analysis of these seismicity phases does not guarantee against false anomalies or failures-to-predict, yet when used in combination, these phases are useful for clarifying the physical nature of seismicity precursors, locating potential earthquake sources, monitoring the evolution of these sources, and for intermediate-term prediction.